“Educação étnico-racial no ensino de artes visuais” - Novais, Karyna Barbosa (2019)
This Research explores some experiences with education for ethnic-racial relations obtained through art/education, carried out with elementary school students from the Escola Municipal Professor Jacy de Assis, from the Municipal Network of Uberlândia (MG) that They stimulated some reflections on the possibility of contributing these experiences to ethnic-racial education in the teaching of Visual Arts. The implementation of the Law 10639/2003, which makes the teaching of African History and African-Brazilian History and Culture compulsory in primary education, motivated studies on education for ethnic-racial relations and an anti-racist education that provided the Survey of the data that culminated in the realization of this research. The search for the processes of construction of pedagogical experiences with ethnic-racial education, led to an expansion of my knowledge and consequently of my didactics in the classroom. It Also directed the empirical paths that I used in the aforementioned school from the writing in 2012 of the "Project Roots of Africa" that was incorporated into the school's Pedagogical political Project (PPP) and guided the annual planning of 2015, referring to the teaching of Discipline of Visual Arts, besides its unfolding in the Workshops of Visual Arts in Afro-Brazilian Culture in the year 2017. Thus, in view of the perspectives of compliance with law 10639/2003 in the teaching of Visual Arts, I performed a pioneering work of pedagogical intervention in the Escola Municipal Professor Jacy de Assis, in Uberlândia (MG), using the experiences obtained with a Group of elementary school students to write this text. In the same sense, I adopted some methodological approaches that went through a bibliographic review on the education of Visual Culture in the multicultural, intercultural and interdisciplinary perspective, and also on education for the relations Ethnic-racial. In Addition to the theoretical dialogues with authors who work with an approach in the anti-racist perspective, this research also included a fieldwork carried out through the Workshops of Visual Arts in Afro-Brazilian Culture, with students from the school The aforementioned Municipal Council. Thus, in the whole of this dissertation I used the processes of qualitative research from the perspective of Action Research and the Triangular Approach, in order to perform some critical and reflexive analyses. In This way, I present in the final considerations the perceptions obtained from the educational process developed in the daily routine of the public school, relating it to the research in Visual Arts, in order to visualize practices and possible actions for education Anti-racist, such as: The questioning of Eurocentric markers, awareness of difference and for racial, cultural and gender diversity, in addition to the perception of identity, the formation of a black conscience and the development of alternatives To confront and overcome racism that can stimulate other education professionals to invest in education for ethnic-racial relations in the teaching of Visual Arts.